HISTOMORPHOMETRY OF EOSINOPHILS AND ERYTHROCYTES OF CONVENTIONALLY REARED BALI CATTLE - Titi Humairah Bahtiar; Ni Ketut Suwiti; I Ketut Suatha (Buletin Veteriner Udayana, 2024)
Blood tissue is an indicator of the health status of Balinese cattle. The presence of red blood cells or erythrocytes and white blood cells such as eosinophils is very important because they play a role in the infection process. Therefore, this study aims to determine the histology and morphometry of eosinophils and erythrocytes as well as the number of eosinophils in Balinese cattle raised in a conventional way. The samples used were 30 cows, taken from Balinese cows raised in Bulian Village, Kubutambahan District, Buleleng Regency. The blood tissue was prepared with MDT staining. Morphometric measurement of eosinophil and erythrocyte white blood cells using EP View application with 1000x magnification. Counting the number of eosinophils was done per 100 leukocyte cells. The results showed that eosinophils were round in shape and had a purplish-colored 2-lobed nucleus and bright pink granulated cytoplasm with an average diameter of 5.90 ± 1.04 µm. Erythrocytes have a discocyte shape without a purple nucleus and several variations of elliptocyte shapes with a mean diameter of 3.62 ± 0.19 µm. The mean white blood cell eosinophils of conventionally reared Balinese cattle was 7%. Further research is needed to assess health status by looking at other indicators such as physiological status in conventionally reared Balinese cattle.